Reappraisal of the role of postoperative radiation therapy in patients with pIIIa‐N2 non‐small cell lung cancer: A propensity score matching analysis. Issue 5 (29th January 2015) - Cao, Qinchen; Zhang, Baozhong; Zhao, Lujun; Wang, Changli; Gong, Liqun; Wang, Jun; Pang, Qingsong; Li, Kai; Liu, Weishuai; Li, Xue; Wang, Peng; Wang, Ping
Abstract: Background: Reappraisal of the role of postoperative radiotherapy in pN2 non‐small cell lung cancer (NSCLC) patients according to N1 lymph node involvement. Methods: A total of 218 pIIIa‐N2 NSCLC patients who underwent complete surgical resection with systematic nodal dissections were enrolled. Propensity scores were used for matching N1 involvement. Overall survival (OS) and disease‐free survival (DFS) were analyzed retrospectively. Results: After matching, pN2b patients without N1 involvement (pN0N2b) exhibited better prognoses than those with N1 involvement (pN1N2b) (5‐year OS: 37.5% vs. 7.1%, P = 0.008; 5‐year DFS: 31.8% vs. 4.6%, P = 0.004). Similar results were not detected in pN2a disease (5‐year OS: 37.8% vs. 31.0%, P = 0.517; 5‐year DFS: 27.1% vs. 20.2%, P = 0.788). The five‐year OS of patients who received no adjuvant therapy (22 pN2a cases, 7 pN0N2b, 5 pN1N2b), adjuvant chemotherapy alone (74 pN2a cases, 11 pN0N2b, 17 pN1N2b) or chemoradiotherapy (25 pN2a cases, 7 pN0N2b, 6 pN1N2b) were compared (pN2a: 31.3%, 37.0%, and 32.0%, P = 0.808; pN0N2b: 0.0%, 18.2%, and 71.4%, P = 0.108; pN1N2b: 0.0%, 0.0%, and 33.3%, P < 0.0001). The five‐year DFS was also analyzed (pN2a: 31.6%, 24.0%, and 18.3%, P = 0.410; pN0N2b: 0.0%, 11.1%, and 57.1%, P = 0.192; pN1N2b: 0.0%, 0.0%, and 16.7%, P < 0.0001). Multivariate analysis revealed that the novel classification based on N1 involvement and pN2a/pN2b staging was an independent prognostic factor of OS and DFS. Conclusion: N1 involvement significantly impacted the prognosis of pN2b NSCLC patients. The benefit of adjuvant therapy in pN2a and pN0N2b patients requires confirmation by further study.